GIARDÍASE EM FELINO - RELATO DE CASO - Nicola, Carolina Ferrazza; Cruz, Fernando Silvério Ferreira Da; Torres, Magda De Souza (Salão do Conhecimento, 2017)
Caso Clínico Apresentado na Disciplina de Terapêutica e Receituário Veterinário